2017
DOI: 10.1111/asj.12845
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transforming growth factor‐β1 treatment on muscle regeneration and adipogenesis in glycerol‐injured muscle

Abstract: Transforming growth factor (TGF)-β1 is associated with fibrosis in many organs. Recent studies demonstrated that delivery of TGF-β1 into chemically injured muscle enhances fibrosis. In this study, we investigated the effects of exogenous TGF-β1 on muscle regeneration and adipogenesis in glycerol-injured muscle of normal mice. Tibialis anterior (TA) muscles were injured by glycerol injection. TGF-β1 was either co-injected with glycerol, as an 'early treatment' group, or injected at day 4 after glycerol, as a 'l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
(60 reference statements)
2
10
0
Order By: Relevance
“…Furthermore, the inhibitory effects of TGFβ1 on intramuscular adipogenesis are time-dependent. Co-injection of TGFβ1 with glycerol presents greater repressive effects than its administration 4 days following glycerol injection (Mahdy et al, 2017). In aggregate, the differentiation fates of intramuscular FAPs are regulated by the intensive interaction with the surrounding macrophages and other immune cells.…”
Section: The Influence Of Immune Cellsmentioning
confidence: 99%
“…Furthermore, the inhibitory effects of TGFβ1 on intramuscular adipogenesis are time-dependent. Co-injection of TGFβ1 with glycerol presents greater repressive effects than its administration 4 days following glycerol injection (Mahdy et al, 2017). In aggregate, the differentiation fates of intramuscular FAPs are regulated by the intensive interaction with the surrounding macrophages and other immune cells.…”
Section: The Influence Of Immune Cellsmentioning
confidence: 99%
“…TGF is also released by adipose tissue and release is enhanced in higher volumes of fat, suggesting that surviving fat grafts would continue to release TGF within wounds to encourage healing. TGF has also been shown in animal models to have a positive effect on adipogenesis therefore suggesting that an increased concentration in PRP may have synergistic effects on both fat survival and wound healing. It has also been shown that PRP stimulates ADSC differentiation into myofibroblasts, crucial cells in the remodelling phase of wound healing, via the TGFβ1‐signalling pathway .…”
Section: Growth Factors and Their Role In Prp And Fat Synergymentioning
confidence: 99%
“…Transforming growth factor (TGF)-β1 induces differentiation of myoblasts into myofibroblasts, proliferation of α-smooth muscle actin (α-SMA), 11,12 and production of extracellular matrix (ECM) proteins. [13][14][15] Increased amount of collagen types 1 (COL-1) and 3 in the Abbreviations: α-SMA, alpha-smooth muscle actin; ANOVA, analysis of variance; AP, alkaline phosphatase; CD, capillary density; C/F, capillary-to-fiber ratio; COL-1, collagen type 1; COL-1α2, collagen type 1α2; COL-3α1, collagen type 3α1; Contra-Den, contralateral denervation hindlimb; Den group, denervation group; Den+10str group, denervation +10 stretches group; Den+60str, denervation +60 stretches group; Den+240str, denervation +240 stretches group; ECM, extracellular matrix; EDL, extensor digitorum longus; GAPDH, glyceraldehyde-3-phosphate dehydrogenase; HE, hematoxylin-eosin; HIF-1α, hypoxia-inducible factor-1 alpha; IgG, immunoglobulin G; Ipsi-Den, ipsilateral denervation hindlimb; mCSA, myofiber cross-sectional area; MHC, myosin heavy chain; MuRF1, muscle-specific RING finger protein-1; PBS, phosphate-buffered saline; PF, picrosirius red-fast green; PFA, paraformaldehyde; qPCR, quantitative real-time polymerase chain reaction; SE, standard error; TGF, transforming growth factor.…”
Section: Introductionmentioning
confidence: 99%